2017
DOI: 10.2337/dc17-0514
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity, Dysmetabolic Traits, and Earlier Onset of Female Puberty in Adolescent Offspring of Women With Gestational Diabetes Mellitus: A Clinical Study Within the Danish National Birth Cohort

Abstract: OBJECTIVEOffspring of pregnancies affected by gestational diabetes mellitus (GDM) are at increased risk of the development of type 2 diabetes. However, the extent to which these dysmetabolic traits may be due to offspring and/or maternal adiposity is unknown. We examined body composition and associated cardiometabolic traits in 561 9- to 16-year-old offspring of mothers with GDM and 597 control offspring.RESEARCH DESIGN AND METHODSWe measured anthropometric characteristics; puberty status; blood pressure; and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
120
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(136 citation statements)
references
References 43 publications
(45 reference statements)
6
120
1
2
Order By: Relevance
“…Today, several studies support the association between GDM and long-term health outcomes in the offspring. Moreover, a recent study by Grunnet and colleagues [21], including 600 offspring of mothers with GDM confirmed the evidence of insulin resistance and obesity, and further showed higher systolic blood pressure and an earlier onset of puberty among the GDM female offspring compared with control offspring. Longterm follow-up studies in groups of offspring of women with GDM indicate that the offspring are more likely to be overall and centrally obese, and to exhibit insulin resistance and glucose intolerance in early adulthood [18].…”
Section: Offspringmentioning
confidence: 61%
See 1 more Smart Citation
“…Today, several studies support the association between GDM and long-term health outcomes in the offspring. Moreover, a recent study by Grunnet and colleagues [21], including 600 offspring of mothers with GDM confirmed the evidence of insulin resistance and obesity, and further showed higher systolic blood pressure and an earlier onset of puberty among the GDM female offspring compared with control offspring. Longterm follow-up studies in groups of offspring of women with GDM indicate that the offspring are more likely to be overall and centrally obese, and to exhibit insulin resistance and glucose intolerance in early adulthood [18].…”
Section: Offspringmentioning
confidence: 61%
“…Specifically, Danish studies have shown that offspring (aged 18-27 years) of women with GDM have an eight-fold higher risk of Type 2 diabetes/prediabetes, a two-fold higher risk of overweight and a five-fold higher risk of metabolic syndrome than offspring from the background population [19,20]. Moreover, a recent study by Grunnet and colleagues [21], including 600 offspring of mothers with GDM confirmed the evidence of insulin resistance and obesity, and further showed higher systolic blood pressure and an earlier onset of puberty among the GDM female offspring compared with control offspring.…”
Section: Offspringmentioning
confidence: 99%
“…These findings are comparable with those of an analysis of 96 male and female Polish youth aged 7 to 16 years wherein Wilk et al detected unadjusted differences of 19.0 and 14.2 mg/dL higher total and LDL cholesterol, respectively, among GDM‐exposed (n = 50) vs unexposed participants (n = 46). In a recent study of greater than 1000 boys and girls in the Danish National Birth Cohort, Grunnet et al reported higher serum triglycerides (5% [95% CI, 1‐10%]) and lower HDL (−0.07 [95% CI, −0.11 to −0.02] mmol/L), as well as marginally higher LDL (0.06 [95% CI, −0.01 to 0.14] mmol/L) at 12 years of age among GDM‐exposed youth . However, these associations became null after adjusting for maternal and child BMI.…”
Section: Discussionmentioning
confidence: 99%
“…In utero exposure to GDM corresponded with an average of 0 to 0.14] mmol/L) at 12 years of age among GDM-exposed youth. 16 However, these associations became null after adjusting for maternal and child BMI.…”
Section: Girlsmentioning
confidence: 99%
“…The populations studied were predominantly Caucasian. Four studies had comparable primary objectives to our review question, (26)(27)(28)(29) two studies looked at multiple predictors of pubertal timing (24,30), and one looked at multiple developmental outcomes in the offspring of mothers with GDM including pubertal timing (25).…”
Section: Study Characteristicsmentioning
confidence: 99%